Exploring the perceptual experiences of nurses regarding the care of patients with COVID-19: A mixed methodological approach - Vaishali S. Jadhav; Arunima Sreeletha; Natasha Mahajan (MGM Journal of Medical Sciences)
Background: The COVID-19 pandemic, with its rapid spread and subsequent lockdown measures, has brought about unprecedented changes in our lives. Terms like lockdown, social distancing, and quarantine have become part of our daily vocabulary. Amid this crisis, frontline workers, including nurses, have emerged as the unsung heroes, bravely battling the effects of the pandemic. This study delves into the perceptual encounters of nurses regarding patient care during this critical period, providing valuable insights into their experiences. Materials and Methods: This study employed a unique mixed-methods sequential explanatory design. Quantitative data was gathered from 202 registered nurses attending to COVID-19 patients in designated hospitals in Navi Mumbai. Following quantitative analysis, samples of qualitative data were collected until data saturation, focusing on experiences categorized as fair or adverse. Quantitative data collection relied on self-reporting, while qualitative data collection involved in-depth telephone interviews and audio recording techniques. The study’s scope was confined to hospitals in Navi Mumbai and specifically targeted staff nurses providing care for COVID-19 patients. Results: 39% of respondents reported experiencing fair situations, while 69% of nurses expressed encountering negative experiences related to COVID-19. The study identified various themes, including encountered challenges, physical hardships, emotional conflicts, provided facilities, and most importantly, the robust support systems. Challenges included caring for immobile patients, insufficient staffing, and extended work hours. Mental concerns comprised fear of contracting the virus, stress, familial tensions, separation anxiety, and disrupted communication with loved ones. The provided facilities encompassed meals, transportation, lodging, personal protective equipment, and amenities such as air conditioning and hot water. Support was observed from colleagues, friends, family, and senior staff members, highlighting the strength of the healthcare community in times of crisis. Social resistance included pressure to resign, lack of familial support, and societal stigma. Coping mechanisms involved communicating with loved ones, receiving support from colleagues, and engaging in activities such as listening to music, meditation, prayer, exercise, and yoga. The study found no significant association between nurses’ perceptual experiences and selected demographic variables. Conclusion: The study examined the perspectives of staff nurses regarding their duties during the COVID-19 pandemic, capturing their experiences through quantitative and qualitative analyses that addressed notable challenges, including physical, mental, and social obstacles.